2007
DOI: 10.1002/eat.20436
|View full text |Cite
|
Sign up to set email alerts
|

Classification of eating disorders: Toward DSM-V

Abstract: Objective: A goal of the DSM-IV revision is to increase clinical and research utility by improving diagnostic validity through reliance on empirical evidence. Currently defined eating disorder (ED) categories have limited validity and require refinement based on data. Method:The available scientific evidence is considered in evaluating the current ED nosology.Results: Specific recommendations include modifying ED classification by retaining categories but adding a dimensional component; removing the amenorrhea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
117
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(134 citation statements)
references
References 29 publications
3
117
0
7
Order By: Relevance
“…Physical abuse were incidents separate from sexual abuse that included life-threatening physical attack with the intent to kill or seriously injure or other physical abuse, such as being beaten, kicked, or burned. We constructed a summary measure of number of lifetime traumas by assigning 1 point for each of the following: (1) child sexual abuse, (2) adult sexual abuse, (3) life-threatening attack, (4) other physical abuse, (5) parental alcohol/drug abuse or mental illness, (6) foster care, reform school/prison before age 18, (7) lifethreatening illness or accident, (8) child having life-threatening illness or death, (9) close friend or family member killed by drunk driver or murdered, and (10) parents or sibling deaths before the subject was 18. This scale has been widely used; subjects experiencing more trauma in all categories have been shown to have higher rates of medical conditions, poorer health, and psychological dysfunction.…”
Section: Edinburgh Postnatal Depression Scale (Epds)mentioning
confidence: 99%
See 1 more Smart Citation
“…Physical abuse were incidents separate from sexual abuse that included life-threatening physical attack with the intent to kill or seriously injure or other physical abuse, such as being beaten, kicked, or burned. We constructed a summary measure of number of lifetime traumas by assigning 1 point for each of the following: (1) child sexual abuse, (2) adult sexual abuse, (3) life-threatening attack, (4) other physical abuse, (5) parental alcohol/drug abuse or mental illness, (6) foster care, reform school/prison before age 18, (7) lifethreatening illness or accident, (8) child having life-threatening illness or death, (9) close friend or family member killed by drunk driver or murdered, and (10) parents or sibling deaths before the subject was 18. This scale has been widely used; subjects experiencing more trauma in all categories have been shown to have higher rates of medical conditions, poorer health, and psychological dysfunction.…”
Section: Edinburgh Postnatal Depression Scale (Epds)mentioning
confidence: 99%
“…EDs disproportionately affect young women of reproductive age within the general population, 5,6 and genetic studies have revealed a significant genetic correlation between EDs and major depressive disorder (MDD), suggesting that the two disorders may be influenced by shared genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] One of the biggest problems is that the majority of eating-disordered individuals meet some, but not all, of the criteria for anorexia nervosa or bulimia nervosa (BN) and thus are classified as having an eating disorder not otherwise specified (EDNOS). 4,[6][7][8][9] Although EDNOS is the most common eating disorder diagnosis in both clinical and research settings, it is not usually included in estimates of eating disorders, 10,11 thus resulting in a deceptively low prevalence of eating disorders.…”
mentioning
confidence: 99%
“…Seseorang yang memiliki persepsi tubuh negatif menganggap tubuhnya tidak menarik, merasa malu, dan tidak percaya diri terhadap bentuk tubuhnya sendiri. (6,7) Eating disorders (gangguan makan) adalah suatu sindrom yang ditandai oleh pola makan yang menyimpang terkait dengan karakteristik psikologik yang berhubungan dengan makan, bentuk tubuh, dan berat badan. Saat ini ada dua macam eating disorder (gangguan makan) yang diakui, yaitu anorexia nervosa dan bulimia nervosa.…”
Section: Pendahuluanunclassified
“…Kebanyakan adalah mirip dengan anoreksia atau bulimia tetapi dengan karakter yang berbeda sedikit. Binge-eating disorder, yang menerima peningkatan dalam jumlah penelitian dan perhatian media dalam beberapa tahun belakangan ini adalah salah satu tipe EDNOS termasuk dalam DSM-V. (7)(8)(9) Persepsi tubuh yang negatif yang dapat berkembang menjadi eating disorders banyak terjadi pada remaja. Menurut World Health Organization (WHO) masa remaja terbagi atas masa remaja awal (early adolescence) berusia 10-13 tahun, masa remaja tengah (middle adolescence) berusia 14-16 tahun dan masa remaja akhir (late adolescence) berusia 17-19 tahun.…”
Section: Pendahuluanunclassified